Diet and estradiol level in adolescent girls - Ririn Hariani; Saptawati Bardosono; Ratna Djuwita; Noorwati Sutandyo; Melani Kumala; Ali Sungkar; Rini Sekartini (Indonesian Pediatric Society, 2016)
AbstractBackground Nutritional intake in adolescent girls in Indonesia has been well studied, but there has been little study on its influence on serum estradiol levels. A high estradiol level has been associated with higher risk of breast carcinogenesis.Objective To evaluate the influence of dietary factors on serum estradiol concentration in adolescent girls.Methods A community-based survey was conducted in female junior high school students in Jakarta from January 2014 to January 2015. Nutritional intake was assessed by semi-quantitative food frequency questionnaires (FFQ), which included the intake of total energy (kcal), carbohydrate (g), protein (g), fat (g), fiber (g), and phytoestrogen (g). Based on the Indonesian recommended daily allowance (RDA), energy and nutrient intakes were categorized as minimal (<70%), low (70-99.9%), normal (100-129.9%), and high (≥130%). Serum estradiol levels were measured during the follicular phase using an enzyme-linked immunosorbent assay (ELISA).Results A total of 189 girls aged 13-15 years were enrolled from 8 junior high schools across the municipalities of Jakarta. Twenty-eight (14.8%) subjects were overweight or obese. Median estradiol level was 41.83 (range 13.14-136.5) pg/mL. Serum estradiol level was significantly correlated with energy, protein, and fat intake. Estradiol level was also significantly associated with carbohydrate (P=0.030) and fat (P=0.036) intake status. Multivariate analysis revealed that intake of energy, protein, and fat, as well as body mass index (BMI) were independent predictors of estradiol levels. However, due to its importance as energy source, we included carbohydrate intake in the final equation to predict estradiol level as follows: E2 = 60.723 – 0.053 (energy) + 0.185 (carbohydrate) + 0.483 (protein) + 0.491 (fat) – 1.081 (BMI).Conclusion Serum estradiol levels in adolescent girls aged 13-15 years are influenced by diet, especially fat intake. Estradiol levels can be predicted from energy, carbohydrate, protein, and fat intake, as well as BMI. [Paediatr Indones. 2016;56:134-8.].